Toughening high-fluidity nylon copolymer as well as preparation method and application thereof
Through the copolymerization method of maleic anhydride grafted polyolefin copolymer and nylon monomer, the problems of fluidity and mechanical properties of existing high-flow nylon materials during the toughening modification process are solved, and the preparation of toughening and high-flowing nylon copolymers is realized, and the comprehensive performance of the material is improved.
Patent Information
- Application Number
- CN202311412389.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
During the toughening modification process of existing high-flow nylon materials, the addition of toughening agents can easily lead to phase separation and anisotropy, which in turn affects the fluidity of the material and the mechanical properties of the final product.
By introducing maleic anhydride grafted polyolefin copolymer with nylon monomer, a toughened and high-flow nylon copolymer is formed, which simplifies the preparation process and avoids additives and oxidation reactions.
The toughening modification of high-flow nylon materials is achieved, which improves the mechanical properties and toughness of the materials, while simplifying the process flow and reducing costs.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The invention relates to a nylon copolymer, and more particularly to a toughened high-fluidity nylon copolymer and a preparation method and application thereof. Background Art
[0002] Nylon materials have good performance and are widely used in the automotive, electronic and electrical industries. With the increasing demand for lightweight vehicles, more and more metal materials are replaced by nylon. At the same time, these industries also put forward higher requirements for the performance of nylon products. The development of high-strength and high-fluidity nylon materials has become a hot spot for product development in the automotive industry and the electrical market.
[0003] High-flow nylon 6 resin refers to nylon 6 resin with low melt flow index, easy molding, short molding time, low energy consumption and cost, and suitable for glass fiber reinforcement. The wall thickness of high-flow nylon parts can be designed to be thinner, shortening the crystallization time and cooling time, greatly shortening the molding cycle, and reducing energy consumption. In addition, improving the flowability of the resin melt improves the impregnation when high glass fiber filling is used, thereby also improving the appearance of the product. The difficulty and key is to reduce the viscosity of the nylon melt without negatively affecting the material properties.
[0004] In order to meet the needs of different fields, high-flow nylon usually needs to be further modified to improve certain performance aspects, such as toughness, low-temperature resistance, etc. However, the addition of toughening agents usually leads to phase separation and anisotropy. Excessive addition of toughening agents can make its fluidity worse, resulting in problems such as high internal stress and easy shrinkage during processing and molding, resulting in poor mechanical properties of the final product. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art, and to provide a toughened high-flow nylon copolymer and a preparation method and application thereof, wherein the preparation method introduces a maleic anhydride grafted polyolefin copolymer to perform in-situ modification of nylon, and obtains toughened and modified high-flow nylon in one step, which simplifies the process, is simple to operate, and improves economic benefits. In addition, the preparation method avoids oxidation of additives and nylon, and can reduce reaction procedures, save reaction time, and improve work efficiency. The high-flow copolymer of the present invention has better mechanical properties and toughness.
[0006] The first aspect of the present invention is to provide a nylon copolymer, comprising an olefin polymer segment and a nylon segment derived from a nylon monomer; wherein the olefin polymer segment has a group derived from maleic anhydride, and the group derived from maleic anhydride is connected to the nylon segment.
[0007] In the nylon copolymer, since the olefin polymer is polymerized into the structure of nylon by a copolymerization method, the high-flow nylon prepared by a small-molecule branching agent has better toughness and thus has better comprehensive performance.
[0008] In a preferred embodiment of the present invention, the molar ratio of the group derived from maleic anhydride to the nylon structural unit in the nylon copolymer is (2-10):100; more preferably,
[0009] The molar ratio of the group derived from maleic anhydride to the nylon structural unit is (2.5-4):100.
[0010] In the present invention, the group derived from maleic anhydride refers to
[0011] In a preferred embodiment of the present invention, the olefin polymer segment is derived from a maleic anhydride grafted olefin polymer; more preferably,
[0012] The maleic anhydride grafted olefin polymer is a maleic anhydride grafted polyolefin and / or a maleic anhydride grafted polyolefin elastomer; more preferably, it is at least one of the following polymers grafted with maleic anhydride: polypropylene, polyethylene, polypropylene and / or polyethylene elastomer, butyl rubber, ABS (acrylonitrile-butadiene-styrene copolymer), EPDM (ethylene propylene diene monomer rubber).
[0013] In a preferred embodiment of the present invention, the number average molecular weight of the maleic anhydride grafted olefin polymer is 500-50,000, preferably 700-20,000, and more preferably 1,000-10,000.
[0014] In a preferred embodiment of the present invention, the molar content of the structural units derived from maleic anhydride in the maleic anhydride grafted olefin polymer is 0.1%-30%, preferably 0.3% to 20%.
[0015] In the present invention, the nylon monomer is at least one nylon monomer having the following structure:
[0016] NH3-R7-NH3 formula (2-1);
[0017] R'OOC-R8-COOR" formula (2-2);
[0018] R"'OOC-R9-NH3 formula (2-3);
[0019]
[0020] NH3-R7'-NH4 + - -OOC-R8'-COOH formula (2-5);
[0021] In formula (2-1) to formula (2-5), R7, R8, R7', R8', R9 and R10 are each independently C1-C 20 One of aromatic hydrocarbons, straight-chain hydrocarbons or branched-chain alkanes;
[0022] In formula (2-2), R' and R" are each independently selected from a hydrogen atom, a phenyl group, and a C1-C4 alkyl group; preferably, one of H and a butyl group;
[0023] In formula (2-3), R'' is selected from a hydrogen atom, a phenyl group, and a C1-C4 alkyl group; preferably, it is selected from a H group and a butyl group.
[0024] In a preferred embodiment of the present invention, each of R7 and / or R7' is C3-C 12 Aromatic hydrocarbons, straight chain hydrocarbons or branched chain alkanes, preferably C4-C 10 Aromatic hydrocarbons, straight-chain hydrocarbons or branched alkanes, more preferably -(CH2)4-, -(CH2)6-, -(CH2) 10 -; and / or,
[0025] The R8 and / or R8' are each C1-C 10 An aromatic hydrocarbon, a straight-chain hydrocarbon group or a branched hydrocarbon group, preferably a C2-C8 straight-chain hydrocarbon group, more preferably -(CH2)2-, -(CH2)4-, -(CH2)8-; and / or,
[0026] R9 and / or R10 are each C3-C 12 A straight chain hydrocarbon group, preferably C3-C 10 The straight-chain hydrocarbon group is more preferably -(CH2)3-, -(CH2)8-, or -(CH2)9-.
[0027] In a preferred embodiment of the present invention, when the nylon monomer contains monomers of formula (2-1) and formula (2-2), the molar ratio between the two monomers of formula (2-1) and formula (2-2) is 1:(0.9-1.1); and / or, the nylon monomer contains at least one of monomers of formula (2-3), formula (2-4) and formula (2-5); preferably at least one of caprolactam, aminocaproic acid, aminoundecanoic acid and hexamethylenediammonium adipate.
[0028] In a preferred embodiment of the present invention, the nylon segment derived from the nylon monomer in the nylon copolymer has at least one of the following three structural units:
[0029]
[0030] Where x, y, and z are the molar contents of the three structural units, and R1-R4 are each C1-C 18 Straight chain hydrocarbon, C1-C 18 Branched hydroxyl groups, C6-C 18 One of the aromatic hydrocarbon groups, and R3 and R4 do not have the same structure at the same time;
[0031] x+y+z=1, x, y, z are all greater than or equal to 0; preferably,
[0032] R1 is -(CH2)4-, -(CH2)6- or -(CH2) 10 -; and / or,
[0033] R2 is -(CH2)2-, -(CH2)4- or -(CH2)8-; and / or,
[0034] R3 and R4 are each -(CH2)5- or -(CH2) 10 -.
[0035] In the present invention, preferably, the structural formula of the polyamide segment is That is, the connection order of the structural units corresponding to x, y, and z is not particularly limited in the present invention. Preferably, the nylon copolymer in the present invention is a random copolymer.
[0036] The second aspect of the present invention is to provide a method for preparing the nylon copolymer described in the first aspect, wherein the nylon copolymer is obtained by copolymerizing raw materials including a reactive toughening agent and a nylon monomer; the reactive toughening agent is a maleic anhydride grafted olefin polymer; and the molar ratio of the nylon monomer to the maleic anhydride group in the maleic anhydride grafted olefin polymer is (2-10):100.
[0037] In a preferred embodiment of the present invention, the molar ratio of the nylon monomer to the maleic anhydride group in the maleic anhydride grafted olefin polymer is (2.5-4):100.
[0038] In a preferred embodiment of the present invention, the number average molecular weight of the maleic anhydride grafted olefin polymer is 500-50,000, preferably 700-20,000, and more preferably 1,000-10,000.
[0039] In a preferred embodiment of the present invention, the molar content of the structural units derived from maleic anhydride in the maleic anhydride grafted olefin polymer is 0.1%-30%, preferably 0.3% to 20%.
[0040] According to the present invention, the amount of the maleic anhydride grafted olefin polymer can be metered by the molar ratio of the maleic anhydride group in the maleic anhydride grafted olefin polymer to the nylon monomer, or can be metered according to the proportion in the total mass of the raw materials used for the polymerization reaction. In a preferred embodiment of the present invention, the raw materials used for the copolymerization reaction include maleic anhydride grafted olefin polymer, nylon monomer and optional water, and the total weight of the raw materials for the polymerization reaction is 100%, and the amount of the maleic anhydride grafted olefin polymer is 3%-40%, preferably 8%-38%, and more preferably 10%-25%.
[0041] The raw materials used in the polymerization reaction include maleic anhydride grafted olefin polymer, nylon monomer and optionally added water.
[0042] The polymerization of the nylon copolymer described in the present invention can be at least one of condensation, ring-opening polymerization, anionic polymerization and cationic polymerization, and the existing preparation conditions of the nylon copolymer can be adopted.
[0043] In a preferred embodiment of the present invention, the polymerization reaction is in-situ polymerization.
[0044] The polymerization reaction is carried out under a protective atmosphere, which includes but is not limited to an inert atmosphere (nitrogen and / or an inert gas).
[0045] In a preferred embodiment of the present invention, the polymerization reaction temperature is 140-280°C, preferably 220-260°C.
[0046] In a preferred embodiment of the present invention, the reaction time is 0.5-24 hours.
[0047] In a preferred embodiment of the present invention, the reaction pressure is 0-20 atmospheres.
[0048] In a more preferred embodiment of the present invention, the conditions of the polymerization reaction include:
[0049] The antistatic nylon copolymer and the nylon monomer are stirred and reacted at 240-260° C. under a protective atmosphere for 0-3 hours; preferably, the reaction is carried out at 0-20 atmospheres for 0-6 hours, preferably 0-2 hours, and then the pressure is reduced to maintain the reaction temperature at 180-280° C., and then high vacuum is started, and the vacuum degree is further reduced to below 2000 Pa to carry out the reaction.
[0050] More specifically, the polymerization method of the present invention is described using nylon 6 as an example:
[0051] The copolymer, nylon 6 monomer caprolactam and water are added into a reactor, and an inert gas is introduced therein to perform deoxygenation treatment;
[0052] The temperature is raised to 180-260° C. to carry out polymerization reaction, and the reaction temperature is finally controlled between 240 and 260° C. and stirred for reaction. The preferred stirring reaction time is 0-3 h.
[0053] During the reaction, the pressure can be maintained at 0-20 atmospheres, maintained at high vacuum for 0-6 hours, and then slowly reduced to maintain the reaction temperature at 180-260°C. Preferably, the low vacuum reaction time is 0-2h, and then high vacuum is started, and the vacuum degree is further reduced to 2000Pa, and the reaction is carried out for a certain time (for example, 0.5-2h). Preferably, the inert gas is nitrogen, and the deoxygenation treatment time is 30min.
[0054] The third aspect of the present invention is to provide an application of the nylon copolymer described in the first aspect or the nylon copolymer obtained by the preparation method described in the second aspect in the fields of automobiles, electronics and electrical appliances.
[0055] The beneficial effects of the present invention are:
[0056] The present invention uses a one-step reaction to copolymerize a toughening agent (maleic anhydride grafted olefin polymer) as an initiator with a nylon monomer to generate a high-fluidity nylon copolymer, which itself has a good toughening effect. The method is simple, and the product has excellent mechanical properties. Compared with conventional high-fluidity nylon, it has better comprehensiveness that can adapt to a wide range of market demands. Compared with adding a toughening agent during the processing, the compatibility is increased, which brings about a better toughening effect.
[0057] The high-fluidity nylon prepared by the method has better mechanical properties and toughness. This is because the method adopts a polymerization method to prepare the copolymer of nylon and polyolefin by chemical reaction, and the reaction process is homogeneous, so the maleic anhydride grafted polyolefin copolymer is more uniformly dispersed, and thus shows better performance in mechanical strength and elongation at break.
[0058] When the dosage of the maleic anhydride polypropylene polymer used in the present invention is relatively low, a nylon material with high viscosity and high melt strength is obtained, which is also an important application of the maleic anhydride graft copolymer in nylon. DETAILED DESCRIPTION
[0059] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0060] The specific embodiments of the present invention are described in detail below.It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not intended to limit the present invention.The endpoints and any values of the scope disclosed in this article are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values.For numerical ranges, between the endpoint values of each scope, between the endpoint values of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered to be specifically disclosed in this article.
[0061] The tensile strength was measured according to the ASTM D638 method at a tensile speed of 50 mm / min;
[0062] Elongation at break is the ratio of the displacement value at break to the original length, expressed as a percentage;
[0063] Flexural strength and flexural modulus were measured according to ASTM D790 method, with a test speed of 2 mm / min;
[0064] Izod notched impact strength was measured according to ASTM D256 method, 3.2 mm thick specimen;
[0065] The Vicat softening temperature is measured according to ASTM D1525 method, with a heating rate of 50°C / min and a load of 5 kg.
[0066] The microstructure of the polymer was measured using an AVANCE DRX400 MHz nuclear magnetic resonance instrument from Bruker, Switzerland. The measurement was performed at room temperature using hydrogen nuclear magnetic resonance spectroscopy, the solvent was deuterated formic acid, and the sample concentration was 10 mg / mL.
[0067] Relative viscosity test of nylon copolymer: The molecular weight of the nylon copolymer of the present invention is characterized by relative viscosity test. Weigh 0.25g polymer sample, put it into a 25ml volumetric flask, add concentrated sulfuric acid (not to the scale line), and after the sample is completely dissolved, add concentrated sulfuric acid to the liquid level in the volumetric flask to the scale line, and then shake it well for measurement; use a pipette to measure 10ml of the prepared solution and add it to the Ubbelohde viscometer (4-1.0-1.1), install the viscometer vertically in a constant temperature water bath at 25±0.5℃ and keep the temperature constant for 20min. The time when the solution flows through the two scale lines of the viscometer is the flow time of the solution. Each sample is measured 3 times (the error before and after does not exceed ±0.2S), and the average value is taken.
[0068] Monomer composition: The microstructure of the polymer was measured using an AVANCE DRX400 MHz nuclear magnetic resonance instrument from Bruker, Switzerland. The measurement was performed at room temperature using hydrogen nuclear magnetic resonance spectroscopy. The solvent was deuterated chloroform and the sample concentration was 10 mg / mL.
[0069] In the following examples, the content of the structural unit derived from maleic anhydride in the maleic anhydride grafted polypropylene is 10 mol%, the molecular weight Mn=9100, and it is a commercially available product.
[0070] Example 1
[0071] A nylon copolymer is prepared by polycondensation of the following components in parts by weight:
[0072] Maleic anhydride grafted polypropylene with a mass content of 10%, the maleic anhydride content in the maleic anhydride grafted polypropylene is 10 mol%, and the molecular weight Mn=9100;
[0073] 85% by mass of monomeric caprolactam;
[0074] Deionized water with a mass content of 5%;
[0075] The preparation method of the nylon copolymer is as follows:
[0076] The weight portion of maleic anhydride grafted polypropylene, monomer caprolactam and water (total 200 g) are added into a polymerization kettle, and the temperature is raised to 240-260° C. for ring-opening polycondensation reaction, and the pressure is controlled to be less than 0.5 MPa. After the reaction takes 2 hours, the pressure is gradually reduced to normal pressure to remove by-product water, and the pressure is further reduced to 2000 Pa and maintained for 2 hours for further polycondensation to increase the molecular weight. The reaction is terminated, and finally the nylon copolymer product B1 is obtained by cooling and pelletizing.
[0077] Example 2
[0078] A nylon copolymer is prepared by polycondensation of the following components in parts by weight:
[0079] Maleic anhydride grafted polypropylene with a mass content of 15%, a maleic anhydride content of 10 mol%, and a molecular weight of Mn=9100;
[0080] 80% by mass of monomeric caprolactam;
[0081] 5% water by mass;
[0082] The polymerization conditions were the same as those in Example 1, and the obtained nylon copolymer was B2.
[0083] Example 3
[0084] The same as in Example 1, the amount of maleic anhydride grafted polypropylene was increased to 20%, the amount of caprolactam was 75%, and the rest was water, and the obtained nylon copolymer was B3.
[0085] Example 4
[0086] The same as in Example 1, the amount of maleic anhydride grafted polypropylene was increased to 25% by weight, the amount of caprolactam was 70% and the rest was water, and the obtained nylon copolymer was B4.
[0087] Example 5
[0088] As in Example 1, the maleic anhydride grafted polypropylene was increased to 35% by mass, the amount of caprolactam was 60%, and the rest was water, to obtain a nylon copolymer B5.
[0089] Comparative Example 1
[0090] The polymerization conditions were the same as those in Example 1, but maleic anhydride grafted polypropylene was not added. A branching agent, diethylenetriamine, was used (raw material ratio: branching agent content 1 wt%, water 4 wt%, caprolactam 95 wt%, a total of 200 g) to prepare a high-flow nylon with the same relative viscosity of 2.0; after the preparation of the nylon, 90 parts of high-flow nylon were selected by weight, and 10 parts of the same maleic anhydride grafted polypropylene as in Example 1 were added by a single screw for blending, i.e., the maleic anhydride grafted polypropylene had a maleic anhydride content of 10 mol% and a molecular weight of Mn=9100; after melt blending, mechanical properties were tested, and the polymer was C1.
[0091] Comparative Example 2
[0092] The polymerization conditions were the same as those in Example 1, but maleic anhydride grafted polypropylene was not added. A branching agent, diethylenetriamine, was used (raw material ratio: branching agent content 1.4wt%, water 4wt%, caprolactam 94.6wt%, a total of 200g) to prepare a high-flow nylon with a relative viscosity of 1.8. After the preparation of the nylon, 85 parts of high-flow nylon were selected by weight, and 15 parts of the same maleic anhydride grafted polypropylene as in Example 1 were added using a single screw for blending, i.e., the maleic anhydride grafted polypropylene had a maleic anhydride content of 10% and a molecular weight Mn=9100. After melt blending, mechanical properties were tested, and the polymer was C2.
[0093] Comparative Example 3
[0094] The polymerization conditions were the same as those in Example 1, but maleic anhydride grafted polypropylene was not added. A branching agent, diethylenetriamine, was used (raw material ratio: branching agent content 1.6wt%, water 4wt%, caprolactam 94.4wt%, a total of 200g) to prepare a high-flow nylon with a relative viscosity of 1.6. After the nylon preparation was completed, 80 parts of high-flow nylon were selected by weight, and 20 parts of the same maleic anhydride grafted polypropylene as in Example 1 were added using a single screw for blending, i.e., the maleic anhydride grafted polypropylene had a maleic anhydride content of 10mol% and a molecular weight of Mn=9100. After melt blending, mechanical properties were tested, and the polymer was C3.
[0095] Example 6
[0096] The same as Example 1, based on the mass content, the maleic anhydride grafted polypropylene is increased to 15%, the amount of caprolactam is 30%, the amount of aminoundecanoic acid is 30%, and the rest is water to obtain the product. The obtained nylon copolymer is B6.
[0097] Example 7
[0098] As in Example 1, maleic anhydride grafted EPDM (commercially available product) was used to replace maleic anhydride grafted polypropylene, wherein the molar content of maleic anhydride in the maleic anhydride grafted EPDM was 5%, the amount of caprolactam was 85%, and the rest was water. The obtained nylon copolymer was B7.
[0099] Example 8
[0100] The same as in Example 1, the maleic anhydride grafted polypropylene was increased to 2% by mass, the amount of caprolactam was 85%, and the rest was water, to obtain a product. The obtained nylon copolymer was B8.
[0101] Table 1
[0102]
[0103]
[0104] Generally speaking, the relative viscosity of linear nylon is above 2.2, and the tensile strength is above 60MPa, and the viscosity is relatively high; when the relative viscosity is reduced to 2.0 or below, the tensile strength and elongation at break of nylon will generally decrease significantly, and the tensile strength may even drop to below 30MPa, and the elongation at break may drop to below 20%, or even below 15%.
[0105] As can be seen from the data in Table 1, compared with conventional high-flow nylon 6 copolymers, the viscosity of the novel nylon of the present invention decreases, and the mechanical properties are still maintained to a certain extent. It has been verified that Examples 6 and 7 also have similar results. However, the same type of maleic anhydride grafted polypropylene blended with nylon cannot achieve the same effect as the copolymerization of maleic anhydride grafted polypropylene with nylon monomer. At the same time, compared with the blended C1, C2, and C3 comparative examples, the high-flow nylon prepared by this method has better mechanical properties and toughness. This is because the present invention adopts a polymerization method, and the copolymer of nylon and polyolefin prepared by chemical reaction has a homogeneous reaction process, so the maleic anhydride grafted polyolefin copolymer is more uniformly dispersed, so it shows better performance in mechanical strength and elongation at break. Similarly, when the amount of maleic anhydride polypropylene polymer used in the present invention is low (B8), a nylon material with high viscosity and high melt strength is obtained, which is also an important application of maleic anhydride grafted copolymer in nylon.
[0106] In the present invention, the characteristics of maleic anhydride groups are utilized to copolymerize with nylon, and a large number of nylon chains are connected to the main chain of polyolefin. On the basis of controlling the ratio of the two, the production of multiple nylon chains is controlled, and the chain length of each nylon chain is reduced, so as to finally achieve the purpose of obtaining high-flow nylon.
[0107] The above content is a further detailed description of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, its architecture can be flexible and changeable, and a series of products can be derived. For example, the method can be used in the polyester field, the polyimide field, etc. Just making a few simple deductions or substitutions should be regarded as falling within the scope of patent protection determined by the claims submitted by the present invention.
[0108] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
[0109] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.
[0110] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.
[0111] The endpoints and any values of the scope disclosed in the present application document are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, between the endpoint values of each scope, between the endpoint values of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.
[0112] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.
[0113] Moreover, any embodiment described in this document may be freely combined with one or more other embodiments described in this document, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of the present invention, and should not be regarded as new content that has not been disclosed or anticipated in this document, unless a person skilled in the art considers that the combination is obviously unreasonable.
Claims
1. A nylon copolymer comprising an olefin polymer segment and a nylon segment derived from a nylon monomer; wherein: The olefin polymer segment has a group derived from maleic anhydride, and the group derived from maleic anhydride is connected to a nylon segment.
2. The nylon copolymer according to claim 1, characterized in that: The molar ratio of the group derived from maleic anhydride to the nylon structural unit in the nylon copolymer is (2-10):100, preferably (2.5-4):
100.
3. The nylon copolymer according to claim 1, characterized in that: The olefin polymer segment is derived from a maleic anhydride grafted olefin polymer; preferably, The maleic anhydride grafted olefin polymer is maleic anhydride grafted polyolefin and / or maleic anhydride grafted polyolefin elastomer; more preferably at least one of the following polymers grafted with maleic anhydride: polypropylene, polyethylene, polypropylene and / or polyethylene elastomer, butyl rubber, ABS, EPDM.
4. The nylon copolymer according to claim 3, characterized in that: The number average molecular weight of the maleic anhydride grafted olefin polymer is 500-50000, preferably 700-20000, more preferably 1000-10000; and / or, The molar content of the structural units derived from maleic anhydride in the maleic anhydride grafted olefin polymer is 0.1% to 30%, preferably 0.3% to 20%.
5. The nylon copolymer according to any one of claims 1 to 4, characterized in that: The nylon monomer is at least one nylon monomer having the following structure: NH3-R7-NH3 formula (2-1); R'OOC-R8-COOR" formula (2-2); R"'OOC-R9-NH3 formula (2-3); NH3-R7'-NH4 + - - OOC-R8'-COOH formula (2-5); In formula (2-1) to formula (2-5), R7, R8, R7', R8', R9 and R10 are each independently C1-C 20 One of aromatic hydrocarbons, straight-chain hydrocarbons or branched-chain alkanes; In formula (2-2), R' and R" are each independently selected from a hydrogen atom, a phenyl group, and a C1-C4 alkyl group; preferably, one of H and a butyl group; In formula (2-3), R'' is selected from a hydrogen atom, a phenyl group, and a C1-C4 alkyl group; preferably, it is selected from a H group and a butyl group.
6. The nylon copolymer according to claim 5, characterized in that: The R7 and / or R7' are each C3-C 12 Aromatic hydrocarbons, straight chain hydrocarbons or branched chain alkanes, preferably C4-C 10 Aromatic hydrocarbons, straight-chain hydrocarbons or branched alkanes, more preferably -(CH2)4-, -(CH2)6-, -(CH2) 10 -; and / or, The R8 and / or R8' are each C1-C 10 An aromatic hydrocarbon, a straight-chain hydrocarbon group or a branched hydrocarbon group, preferably a C2-C8 straight-chain hydrocarbon group, more preferably -(CH2)2-, -(CH2)4-, -(CH2)8-; and / or, R9 and / or R10 are each C3-C 12 A straight chain hydrocarbon group, preferably C3-C 10 The straight-chain hydrocarbon group is more preferably -(CH2)3-, -(CH2)8-, or -(CH2)9-.
7. The nylon copolymer according to claim 5, characterized in that: When the nylon monomer contains monomers of formula (2-1) and formula (2-2), the molar ratio between the two monomers of formula (2-1) and formula (2-2) is 1:(0.9-1.1); and / or, The nylon monomer contains at least one of the monomers of formula (2-3), formula (2-4) and formula (2-5); preferably at least one of caprolactam, aminocaproic acid, aminoundecanoic acid and hexamethylenediammonium adipate.
8. A method for preparing the nylon copolymer according to any one of claims 1 to 7, comprising copolymerizing raw materials including a reactive toughening agent and a nylon monomer to obtain the nylon copolymer; the reactive toughening agent is a maleic anhydride grafted olefin polymer.
9. The preparation method according to claim 8, characterized in that: The molar ratio of the nylon monomer to the maleic anhydride group in the maleic anhydride grafted olefin polymer is (2-10):100, preferably (2.5-4):
100.
10. The preparation method according to claim 8, characterized in that: The number average molecular weight of the maleic anhydride grafted olefin polymer is 500-50000, preferably 700-20000, more preferably 1000-10000; and / or, The molar content of the structural units derived from maleic anhydride in the maleic anhydride grafted olefin polymer is 0.1% to 30%, preferably 0.3% to 20%.
11. The preparation method according to any one of claims 8 to 10, characterized in that: The raw materials used in the copolymerization reaction include maleic anhydride grafted olefin polymer, nylon monomer and optional water. Based on the total weight of the raw materials in the polymerization reaction as 100%, the amount of the maleic anhydride grafted olefin polymer is 3%-40%, preferably 8%-38%, and more preferably 10%-25%; And / or, the conditions of the polymerization reaction include: The polymerization reaction is carried out under a protective atmosphere, and / or the polymerization reaction temperature is 140-280° C., preferably 220-260° C.; and / or the reaction time is 0.5-24 hours; and / or the reaction pressure is 0-20 atmospheres.
12. Use of the nylon copolymer according to any one of claims 1 to 7 or the nylon copolymer obtained by the preparation method according to any one of claims 8 to 11 in the fields of automobiles, electronics and electrical appliances.